1997
DOI: 10.1038/bjc.1997.103
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology of breast cancer in relation to age

Abstract: Summary Histological reports of 1869 consecutive women with invasive breast cancer have been reviewed to determine whether histological features of the tumours were related to the patients' age. The patients, treated between 1983 and 1992, were divided into four groups, based on age. There were 148 aged < 39 years, 355 aged [40][41][42][43][44][45][46][47][48][49] years, 984 aged 50-69 years and 382 aged 70 years or more. The most outstanding finding was the increase in incidence of grade IlIl infiltrating duc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
101
2
6

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(117 citation statements)
references
References 17 publications
8
101
2
6
Order By: Relevance
“…This 10 years earlier peak incidence age for Iranian women is different from developed countries (Parkin and Fernandez, 2006;Smigal et al, 2006) but resembles to developing nations (Agarwal et al, 2007) and corresponds with other studies done in Iran (Mousavi et al, 2007;2008;Harirchi et al, 2011). Some biomarker studies and clinical data point that lateonset BC is biologically less aggressive with a slower growth than early-onset (Fisher et al, 1997;Benz, 2008). The current study has supported this idea to some extent.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This 10 years earlier peak incidence age for Iranian women is different from developed countries (Parkin and Fernandez, 2006;Smigal et al, 2006) but resembles to developing nations (Agarwal et al, 2007) and corresponds with other studies done in Iran (Mousavi et al, 2007;2008;Harirchi et al, 2011). Some biomarker studies and clinical data point that lateonset BC is biologically less aggressive with a slower growth than early-onset (Fisher et al, 1997;Benz, 2008). The current study has supported this idea to some extent.…”
Section: Discussionsupporting
confidence: 89%
“…Also, subjects were stratified into five age groups: ≤40 years, 41-50 years, 51-60 years, 61-70 years, and 71≤ years. Cut-off age for young women has varied from 35-40 years in some studies (Fisher et al,1997;Colleoni et al, 2002;Harirchi et al, 2011). We selected 40 years or under, since it provided a group of reasonable size which was compatible with other studies.…”
Section: Methodsmentioning
confidence: 99%
“…One third of operable cases with invasive disease in the current series had metastatic disease in their axillary nodes at diagnosis, which is not as high as Fisher et al, who reported lymph node involvement in 60% of patients aged Ͻ 39 years, 17 Bertheau (65%), 18 Walker in 69% of patients under 30, 9 or Kim et al, who found a 48% node positive rate in patients under 35. 7 The incidence of node positivity in very young women was not statistically different from those aged between 26 and 35 years, which suggests that the low figure of 33% is a reflection of the small sample size.…”
Section: Discussioncontrasting
confidence: 47%
“…If these carcinomas had not been selected in this manner, a higher percentage of high-grade carcinomas would be expected in the premenopausal group and a lower percentage expected in the postmenopausal group. 27,28 In spite of this selection process, the younger, premenopausal group of carcinomas had a higher stage (greater than stage I; p ϭ 0.003), a greater incidence of positive lymph nodes (p ϭ 0.041) and larger tumors (p Ͻ 0.001). There was a higher percentage of Caucasian women (84%) than African American women (16%) who were premenopausal and Յ45 (p ϭ 0.012).…”
Section: Characteristics Of the Study Populationmentioning
confidence: 99%
“…Also, comparisons of the pathology of breast carcinomas have demonstrated that there is a greater proportion of high-grade carcinomas in young women (younger than 40 years) 27,28 and that special histologic types of invasive carcinoma (e.g., mucinous and papillary carcinomas) with more favorable prognoses than the more common infiltrating ductal carcinoma are more prevalent in older than younger populations. 29,30 However, histologic grade and type are closely related to the presence of other prognostic markers, including ER, rate of cell proliferation and p53 status.…”
mentioning
confidence: 99%